Design, synthesis, and biological studies of dual URAT1 inhibitor and FXR agonist based on benzbromarone. (1st December 2022) - Huang, Wanqiu; Jiao, Shixuan; Chen, Siliang; Chen, Ya; Yang, Zhongcheng; Wang, Wenxin; Cao, Zhijun; Li, Zheng; Zhang, Luyong
Graphical abstract: The SBDD was performed to modified the benzbromarone, and the compound 4 was obtained which exhibited superior uric acid-lowering activity. Abstract: With increased unhealthy dietary patterns and a sedentary lifestyle, the prevalence of hyperuricemia is growing rapidly, placing a tremendous burden on the public health system. Persistent hyperuricemia in extreme cases induces gout, gouty arthritis, and other metabolic diseases. Benzbromarone is a potent human urate transporter 1 (URAT1) inhibitor that is widely used as a uric acid-lowering drug. Recent studies indicated that benzbromarone can also activate farnesoid X receptor (FXR), whereas its agonistic activity on FXR is rather poor. Mounting evidence suggested that the etiology of gout is directly related to NOD-like receptor thermal protein domain associated protein 3 (NLRP3) inflammasomes, and FXR suppresses the expression of NLRP3 in various ways. Therefore, the dual URAT1 inhibitor and FXR agonist may exert synergistic effects on decreasing uric acid (UA) levels and inhibiting inflammation. To obtain a better dual URAT1 inhibitor and FXR agonist, we performed the structure-based drug design (SBDD) strategy to improve the FXR activation of benzbromarone by forming strong interactions with ARG331 in FXR binding pocket. All of these efforts lead to the identification of compound 4, which exerts better activity on FXR and uric acid-lowering effect than benzbromarone.